1983
DOI: 10.1002/path.1711410405
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular immune complexes in experimental Mycobacterial BCG granulomas

Abstract: Quantitative results of Mycobacterial BCG antigen, immunoglobulin and complement in rat skin lesions during the evolution of the granuloma reveal peak values of these factors at 49 days. The combination of antigen, Ig and complement, present extracellularly and in polymorphs at this time, indicates immune complex formation at an antigen-antibody ratio which may approximate to equivalence. This development coincides with mass lysis of host macrophages, and is followed by a sharp reduction in the antigen load. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Nothing is known about the pathways leading to the development of granulomas in HCV. It has been shown that immune complexes play a role in the development of granulomas 10 and, as immune complex formation is seen in HCV 11;12 , this is a possible pathogenic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nothing is known about the pathways leading to the development of granulomas in HCV. It has been shown that immune complexes play a role in the development of granulomas 10 and, as immune complex formation is seen in HCV 11;12 , this is a possible pathogenic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies reported the presence of extravascular immune complexes with high bacterial load and low cell-mediated immunity in experimental TB (26). Another study concluded that the antigen/antibody ratio within the lesions might be crucial in modulating the balance between tissue destruction and healing (27).…”
mentioning
confidence: 99%